Hukum sebagai Alat Kekuasaan dalam Studi Kasus Kriminalisasi Petani pada Konflik Agraria di Banyuwangi - Maximiliania Krismarmita Brahman; Nabila Sanina Fadhilah; Anita Raharjayanti; Lia Risqi Ananda (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The agrarian dispute that occurred in Pakel Village, Banyuwangi, illustrates the complexity of legal issues and structural inequalities that still linger from the New Order era. Several local farmers were detained on charges of vandalism and incitement, despite the fact that they were defending ancestral land that had been managed for generations against the unilateral claims of a plantation company. This article examines the incident through the lens of agrarian law, land ownership rights, and principles of social justice, while also analyzing the state's role in balancing the rights of indigenous communities and corporate interests. This case study shows that a repressive legal approach actually deepens inequality and hinders the process of agrarian reform. The conflict in Pakel Village is a clear reflection of the state's inability to handle agrarian conflicts fairly and sustainably.